Echoes of Past Revolutions: Architecture, Memory, and Spectral Politics in the Historic Districts of Port-au-Prince - Vincent Joos (VIBRANT - Vibrant Virtual Brazilian Anthropology, 2020)
This article explores the life history of Ulrick Rosarion, a Haitian federal prosecutor who built his career during the Duvalier dictatorship. Rosarion lived his entire life in a small house of downtown Port-au-Prince, in a neighborhood formerly inhabited by the Black middle-classes that gained prominence in the political and administrative sphere during the dictatorship (1957-1986). Rosarion was also a writer who produced four books of nationalist poetry. Based on interviews and readings of his literary production, and beyond, through an exploration of architectural forms and material remnants echoing the dictatorship, this paper explores how an idealized version of the dictatorship today haunts the political landscape of Haiti. Moreover, this article argues that the state takes on a sensual form that allows for the diffusion and/or rupture of past ideologies.